INVESTIGATION OF THE CHANGE IN THE PHYSICAL PROPERTIES OF NITI SHAPE MEMORY ALLOYS BY ADDING COBALT ELEMENT - ZARDAWI, HANAA SHAHAB AHMED (Fırat Üniveristesi, 2019)
Kobalt elementi katkısı ile NiTi şekil hatırlamalı alaşımların fiziksel özellikleri üzerindeki değişimin incelenmesi Bu çalışmada, atomikçe % 2,3,4,5 ve 6 oranında kobalt elementi katılanan NiTi şekil hatırlamalı alaşımları ark eritme yöntemiyle eritildi ve oda sıcaklığında soğutuldu. Alaşım ingotlarında elementlerin homojen olarak yayılması için 1050 oC de 24 saat fırında hava atmosferinde bekletildi. Alaşımların dönüşüm sıcaklıkları, kristal yapıları, mikroyapısal fazları, kimyasal oran değişimleri ve manyetik özellikleri, DSC (Diferansiyel Taramalı Kalorimetre), x ışınları difraktometresi, optik mikroskop, SEM-EDX cihazı ve PPMS (fiziksel özellik ölçüm cihazı) kullanılarak belirlendi. Sonuçlara göre, atomikçe %2 ve %3 kobalt içeren alaşım, oda sıcaklığında martensit fazda, diğerleri ise austenit fazdadır. Entalpi değişimi bu iki durum için farklılık göstermiştir. Martensit fazda olan alaşımlarda artmış, austenit fazda olan alaşımlarda azalmıştır. Bu azalış, austenit fazda olan alaşımlarda Co katkısını artmasından kaynaklanır. Bununla birlikte oda sıcaklığında alınan manyetizasyon ölçümlerine göre, austenite fazda saturasyon değeri, martensit fazdaki alaşımlara göre daha yüksektir. Anahtar Kelimeler: faz dönüşümü; şekil hatırlamalı alaşım; Kobalt element; Ti2Ni faz; manyetizayon özellikleri; NiTi alaşımı

SUMMARY INVESTIGATION OF THE CHANGE IN THE PHYSICAL PROPERTIES OF NITI SHAPE MEMORY ALLOYS BY ADDING COBALT ELEMENT In this study, The NiTi shape memory alloys which doped with 2, 3, 4, 5, and 6 at.% of cobalt element were melted by using arc-melting technique and cooled down to room temperature naturally. To make all contribution elements spread equally in the prepared alloy's ingots, they were kept at 1050 oC for 24h in a furnace at air atmosphere. By using DSC (Differential Scanning Calorimetry), x-ray diffractometer, optical microscope, SEM-EDX, and PPMS equipment each crystal structure of alloys, the microstructural phases, variation rate in chemical composition, and magnetization properties of the samples determined, respectively. The results showed that alloys with 2, and 3 at.% of cobalt content has martensite phase in room temperature while the others at the same temperature had austenite phase. The enthalpy change found to have different situation for each categories, such that its value increase in martensite phase-alloys, whereas, this value decrease with increasing Co-additive in austenite phase-alloys. Also, magnetization measurement at room temperature showed that austenite phase-alloys have higher magnetization compared with martensite phase-alloys. Keywords: Phase transformation; Shape Memory Alloy; Cobalt element; Ti2Ni phase; magnetization properties; NiTi alloy.
Kobalt elementi katkısı ile niti şekil hatırlamalı alaşımların fiziksel özellikleri üzerindeki değişimin incelenmesi
Keywords: Fizik ve Fizik Mühendisliği